The Impact of Leadership on the Participation of Congregation Member - Juwinner Dedy Kasingku; Winda Novita Warouw; Edwin Melky Lumingkewas (Edumaspul: Jurnal Pendidikan, 2024)
Quality of leadership is highly needed and essential in an organization, including the church. A reliable, responsible, loyal, diligent, and honest leader can have a positive influence on members to collaborate in achieving the church's goals. In the context of Christian leadership, spiritual leaders must demonstrate attitudes and characters by emulating the teachings and examples of Jesus. However, there are many cases where church leaders engage in misconduct and do not set a good example for the congregation, such as cases of sexual violence and other misconducts, resulting in members becoming inactive in the church due to this. This study uses a qualitative method with a literature study approach to find out the influence of leadership on the activity of congregation members. The results show that the views and expectations of congregation members towards leadership are very diverse, but the most important thing is that leaders must serve with full loyalty, patience, and show concern for the congregation members. Factors such as dissatisfaction in service, laziness in worship, family struggles, lack of trust, and busyness in work are the main causes of the inactivity of members in the church. Therefore, effective strategies are needed to provide motivation and support to congregation members to be active and willing to participate in every worship activity, including worship services